Histopathological evaluation of hepatic tissue of yellow Rasbora (Rasbora lateristriata) exposed to paracetamol - Septriani, Nur Indah; Saribu, Ruth Liananda Citra Dolok; Apriliyani, Tia; Karlina, Ina; Pusparini, Nur Ainun Oktavia; Zusrina, Laili Mufli; Sari, Ria Vinola Septhya; Allimi, Hayu Swari; Supraitno, Murtiadi Erlan; Saeed, Faisal; Simanungkalit, Eben Ezer; Paramita, Pradnya; Retnoaji, Bambang; Sofyantoro, Fajar; Wijayanti, Nastiti (Biological Environment and Pollution, 2023)
Excessive consumption of paracetamol may lead to hepatic necrosis, nephrotoxicity, extra-hepatic lesions, and even fatality in both humans and animals. The objective of this study was to examine the histological changes in the hepatocytes of yellow rasbora (Rasbora lateristriata) exposed to paracetamol. The fish were subjected to varying concentrations of paracetamol over a period of four days. Group I served as the control group without any paracetamol exposure. Groups II, III, and IV were exposed to 2, 3, and 4 mg/L of paracetamol, respectively. A total of six individuals were allocated to each of the four experimental groups. The histological analysis of the hepatic tissue following paracetamol exposure at concentrations of 2, 3, and 4 mg/L revealed hepatic damage characterized by picnosis, necrosis, and vacuolization. In summary, higher concentrations of paracetamol were associated with an increase in the severity of histopathological changes in the hepatic tissues of yellow rasbora.